A temporally dynamic examination of research method usage in the Chinese library and information science community. Issue 5 (September 2021) - Lou, Wen; Su, Zilong; He, Jiangen; Li, Kai
Abstract: In this paper, we discuss how research methods are used in the Chinese library and information science (LIS) community, a fundamental question in the pursuit of a global overview of this interdisciplinary research domain. We used manual coding to identify research methods mentioned in 2, 421 Chinese-language papers written by 53 prestigious Chinese LIS researchers across different generations. For all selected publications, we manually identified and classified methods using a modified version of an established classification scheme for LIS research methods. Moreover, we examined how research methods are used by researchers belonging to different age groups over time. We identified a significant shift in the use of methods among examined publications: quantitative methods are increasingly used over time, driven both by the emergence of newer generations of researchers and by senior researchers gradually adopting newer methods. These findings reflect a major, and heretofore undiscussed, shift in research style in the LIS community in China. Our approach facilitates a new, more dynamic discussion of how research methods are adopted in a research community and will greatly contribute to future studies on this topic.